From Alexandria to Harran: the Neoplatonic and Sufi Wisdom - Uždavinys, Algis (Acta Orientalia Vilnensia, 2002)
The essay deals with the relationship between the Islamic philosophy and Hellenism. The influence of the Neoplatonic ideas on the early Islamic culture of spirituality is emphasized, while trying to reveal the common archetypal patterns of the Near Eastern and Mediterranean traditions.